Transformation Strategy of Omni-Channel Marketing (OCM) Based on Digital Innovation to Foster Sustainable Competitive Advantage for MSMEs - Lazuardi, Dedy; Ihdina Gustina; Nurmala Sridewi (Sean Institute, 2025)
Micro, Small, and Medium Enterprises (MSMEs) still rely on conventional marketing strategies that are less effective in enhancing competitiveness. According to data from the Ministry of Cooperatives and SMEs (KemenKopUKM), only 21% of MSMEs have adopted digital approaches, with remaining challenges including limited infrastructure, lack of digital skills, and minimal policy support. Omni-Channel Marketing (OCM) based on digital innovation emerges as a strategic solution to expand market reach, improve business efficiency, and create sustainable competitive advantage. In line with the President's Asta Cita Point 3,